Damage and fractal evolution trends of sandstones under constant-amplitude and tiered cyclic loading and unloading based on acoustic emission - Dongxu Liang; Nong Zhang; Lixiang Xie; Guangming Zhao; Deyu Qian (International Journal of Distributed Sensor Networks)
It is of significance to study the damage and destruction of rock under cyclic loading in geotechnical engineering. We determined the trends in damage evolution of sandstone under constant-amplitude and tiered cyclic loading and unloading under uniaxial compression. The results of the study show that (1) the variation of acoustic-emission events was consistent with the stress curves and 89% of all acoustic-emission events occurred during the cycling stages. The observed Kaiser effect was more notable in tiered cycling. (2) The damage variable increased sharply in the cycling stages and its increment was 0.07 higher for tiered cycling than constant-amplitude cycling. Sandstone exhibited greater damage under tiered cyclic loading and unloading. (3) Equations for the evolution of the damage variable under the two cycle modes were obtained by fitting of experimental data. (4) The fractal dimensions of the constant-amplitude cycle were larger than those of the tiered cycle. The process of damage and destruction presents a trend of reducing fractal dimension. The damage accumulation of sandstone under tiered cycling was faster than under constant-amplitude cycling. These results provide references for damage and early warning of rock under both constant-amplitude and tiered cyclic loading and unloading.